Drought-induced microbial dynamics in cowpea rhizosphere: Exploring bacterial diversity and bioinoculant prospects - Boshra Ahmed Halo; Yaqeen A. S. Aljabri; Mahmoud W. Yaish (PLoS ONE, 2025)
Rhizospheric bacterial communities in plants contribute to drought resilience by promoting plant-soil interactions, yet their biodiversity and ecological impacts are not fully characterized. In cowpeas, these interactions may be crucial in enhancing tolerance to drought conditions. In this study, cowpea plants were subjected to drought treatment, the soil attached to the roots was collected, environmental DNA (e-DNA) was extracted, and the bacterial communities were identified as amplicon sequence variants (ASVs) by metagenomics analysis of the 16S rRNA gene. Microbial communities under drought and control conditions were analyzed using taxonomy and diversity metrics. The sequencing results revealed 5,571 ASVs, and taxonomic analysis identified 1,752 bacterial species. Alpha and beta diversity analyses showed less conserved microbial community structures and compositions among the samples isolated from the rhizosphere under drought conditions compared to untreated samples, implying the enhancement effect of drought on species’ biodiversity and richness. The differential accumulation analysis of the bacterial community identified 75 species that accumulated significantly (P ≤  0.05) in response to drought, including 13 species exclusively present, seven absent, and 46 forming a high-abundance cluster within the hierarchical heatmap. These species were also grouped into specific clades in the phylogenetic tree, suggesting common genetic ancestry and potentially shared traits associated with drought tolerance. The differentially accumulated bacterial list included previously characterized species from drought and saline habitats. These findings suggest that drought stress significantly alters the composition and abundance of epiphytic bacterial communities, potentially impacting the rhizosphere’s ecological balance and interactions with cowpeas. The results highlight microbial adaptations that enhance plant resilience through improved stress mitigation, providing meaningful understandings for advancing sustainable agriculture and developing microbial-based strategies to boost crop productivity in drought-prone regions.